A Case Report on Cervicofacial Subcutaneous Emphysema and Its Management: A Unique Presentation of Congenital Defect of the Foramen of Huschke - Siti Nurafiqah Sharudin; Nor Azirah Salahuddin; Siti Asmat Md Arepen; Noor Azrin Md Anuar; Nor Eyzawiah Hassan; Shahrul Hitam; Fadzilah Ismail; Salina Husain (Springer Science and Business Media LLC; Cureus, Inc, 2024)
Vol. 15, Issue 10 (page: 1-10)